Congestive hepatopathy secondary to graves’ disease: a case report - Adrian, Steven Johanes; Wirawan, I. Made Suma (International Journal of Advances in Medicine, 2022)
Graves’ disease is a common cause of hyperthyroidism in iodine-sufficient parts of the world. Excessive thyroid hormone is known to have multiple effects on various organs, including the liver. We reported a case of 49-year old male patient with worsening jaundice, ascites, tremor, and palpitation, with previous history of uncontrolled Graves’ disease. Findings from examination reveals signs of congestive hepatopathy, such as positive hepatojugular reflux and dilated hepatic vein. Treatment options for hyperthyroidism in patients with liver dysfunction includes methimazole and radioactive iodine-131. Liver dysfunction in patients with thyrotoxicosis is commonly found in daily practice, but establishing the cause of liver dysfunction can be a challenge because of the multiple cause of liver injury in hyperthyroidism.